Altruism, Discourse, and Blood Donation : The rhetoric of "The Gift of Life" - Solomon, Guy Douglas (East Carolina University, 2013)
The American healthcare system has since WWII regularly suffered seasonal shortages of blood donations. This dissertation examines, through the theories of activity systems, genres, frames and social groups, the discourses and rhetoric associated with the practice and social activity of blood donation. The history of the discourse and the activities of intermediaries responsible for recruiting blood donors are examined focusing on significant discontinuities to the activity system of blood donation such as WWII; the shift to an all-volunteer, free donation system; and the threat to the system posed by the advent of HIV/AIDS. Altruism has been posited as "the" motivation for blood donation since the US moved to an all-volunteer donation system. In spite of assurances that the use of an all-volunteer system would result in an increase in blood donations, since 1974 shortages have regularly occurred but no other appeals have been officially tested or implemented by major intermediaries such as the American Red Cross or America's Blood centers. Reasons for this resistance to consider alternatives and possible changes to the system are examined to begin to develop ideas about ways that communication might help remedy these regular shortages.
Keywords: Rhetoric; Organizational behavior; Public policy; Activity theory; Blood donation; Discourse; Genre; Blood donors--United States; Blood banks--United States; Altruism--United States; Discourse analysis